The importance of teamwork climate for preventing burnout in UK general practices. (19th September 2020) - Galleta-Williams, Henry; Esmail, Aneez; Grigoroglou, Christos; Zghebi, Salwa S; Zhou, Anli Yue; Hodkinson, Alexander; Panagioti, Maria
Abstract: This short report aims to investigate the association between teamwork and burnout among general practitioners (GPs). A two-stage survey was conducted. In stage one, validated self-report measures of burnout and teamwork were completed by 50 GPs across 12 general practices in Greater Manchester, UK. In stage two, staff members across 3 of the 12 general practices (GPs, nursing staff, managers and admin staff) responded to free text questions about teamwork ( n = 20). The results of the stage one survey showed that teamwork in GPs was significantly negatively associated with the emotional exhaustion ( r = −0.326, P < 0.05) and depersonalization ( r = −0.421, P < 0.01) domains of the burnout measure and significantly positively associated with the personal accomplishment ( r = 0.296, P < 0.05) domain. Free text responses in stage two were assigned into three themes: (i) addressing organizational barriers which might threaten teamwork, (ii) promoting the view of teamwork as a shared responsibility among all staff members of the general practice and (iii) implementing improvement strategies which can be embedded in the busy environment of general practices. GPs and other staff members of general practices valued the importance of teamwork for boosting their morale and mitigating burnout. Future research should focus on designing and embedding brief teamwork improvement strategies in general practices.